2013
DOI: 10.3109/14767058.2013.765404
|View full text |Cite
|
Sign up to set email alerts
|

The fetal inflammatory response in subgroups of women with preterm prelabor rupture of the membranes

Abstract: A higher fetal inflammatory response mediated by umbilical cord blood IL-6 was identified when both MIAC and HCA were detected in pregnancies complicated by PPROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…These findings are in conflict with a previous study by Yoon et al, which showed an association between oligohydramnios and a higher intra-amniotic inflammatory response (determined by the amniotic fluid IL-6, IL-1β and tumor necrosis factor-α levels) and the fetal inflammatory response (characterized by the umbilical cord blood IL-6 levels) [13]. Our previous studies showed that the highest intra-amniotic and fetal inflammatory responses in pregnancies characterized by PPROM are elicited when both MIAC and HCA are present [7], [34]. In this study, we found no difference in the presence of women with both MIAC and HCA between the groups with and without oligohydramnios [with oligohydramnios 25% (10/40) vs. without oligohydramnios 21% (7/34); p  = 0.78; data not shown] [7], [13], [34].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings are in conflict with a previous study by Yoon et al, which showed an association between oligohydramnios and a higher intra-amniotic inflammatory response (determined by the amniotic fluid IL-6, IL-1β and tumor necrosis factor-α levels) and the fetal inflammatory response (characterized by the umbilical cord blood IL-6 levels) [13]. Our previous studies showed that the highest intra-amniotic and fetal inflammatory responses in pregnancies characterized by PPROM are elicited when both MIAC and HCA are present [7], [34]. In this study, we found no difference in the presence of women with both MIAC and HCA between the groups with and without oligohydramnios [with oligohydramnios 25% (10/40) vs. without oligohydramnios 21% (7/34); p  = 0.78; data not shown] [7], [13], [34].…”
Section: Discussionmentioning
confidence: 95%
“…The presence of these conditions is followed by an intra-amniotic and fetal inflammatory response that is associated with an adverse neonatal outcome [3][7]. Early identification of these complications appears to be crucial for the optimal management of PPROM and improved neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…21 PPROM pregnancies complicated by both MIAC and HCA seem to comprise the worst-case scenario subgroup of PPROM because of their highest intraamniotic and fetal inflammatory response. 10,11 In this study, the highest intraamniotic inflammatory response, as determined by amniotic fluid IL-6, peaked when both MIAC and HCA were present. This subgroup of women had a higher amniotic fluid concentration of IL-6 than the remaining 3 subgroups (MIAC alone, HCA alone, and without both MIAC and HCA).…”
Section: Principal Findings Of This Studymentioning
confidence: 96%
“…[3][4][5][6][7][8][9] Our previous work has shown that the presence of both MIAC and HCA is associated with strong intraamniotic and fetal inflammatory response. 10,11 This indicates that this subgroup constitutes the worst case scenario of PPROM.…”
mentioning
confidence: 95%
“…The low rate of antenatal infectious complications may be attributed in part to a relative short latency between diagnosis and delivery (mean = 19 days), which averted the onset of infection in some women. It is also possible that FIRS occurred without microbial invasion of the amniotic cavity in some cases [38] . Lack of correlation between maternal IL-6 levels and a diagnosis of chorioamnionitis in the present study may be due to a combination of the relative rarity of overt antenatal chorioamnionitis and the limited number of subjects in the study.…”
Section: Discussionmentioning
confidence: 99%